Effect of Fermentation Time and Concentration of Rhizopus oryzae on Mass and Quality of Mocaf Flour (Modified Cassava Flour) - Hargiyanti Hargiyanti; Abdul Haris Mulyadi (Universitas Muhammadiyah Purwokerto, 2022)
Cassava is a local food that produces carbohydrates. Cassava can be processed and has great potential to be processed into various food products, one of which is Mocaf. Mocaf is cassava flour made by fermentation, with the principle of modifying cassava cells, this modification can change the mass of Mocaf flour and the best flour content chemically and physically. Mocaf can be used as a substitute for wheat flour. In this study, the production of mocaf was carried out by means of fermentation using variations in the length of time of fermentation and also the amount of concentration of tempeh yeast (Rhizopus oryzae). The time used for fermentation used in this study was 1; 1.5; 2; 2.5; and 3 days. While the amount of yeast used is 2.5; 5; 7.5; 10 and 12.5 grams. The results of this study, especially the mass, are very influential, the longer the fermentation time and the more yeast added, each will produce less flour mass. While the SNI analysis such as water content, ash content, fiber content, degree of acid, HCN content and also color analysis all meet SNI.